Evaluation of Blood Biomaterials Efficacy in the Treatment of Leishmania Lesions - Alireza Moradabadi; Shariati Aref; Taher Azimi; Ehsanollah Ghaznavirad; Alireza Farsinejad (Fasa University of Medical Sciences, 2020)
Background & objective: The aim of this study was to evaluate the therapeutic effect of platelets lysate on leishmaniasis lesions. Materials & methods: In this study, we used hamster as an animal model and Leishmania major to create an infection in vitro condition. The presence of Leishmania in the site of infection was confirmed by Real-time PCR. We investigated the effect of platelet, plasma, and platelets' lysate on leishmaniasis lesions and finally, the therapeutic effects of these biomaterials were screened by histological methods. Results: Real-time PCR method confirmed the presence of parasites in the site of infection. The results of histopathological investigation revealed that in lesions treated with platelet, there were inflammatory response, tissue necrosis and high amount of Leishmania. The wounds extent in both groups treated with plasma and platelet lysate was significantly reduced. However, the result showed that the amounts of Leishmania were significantly reduced in lesions of hamsters treated with platelet lysate. Conclusion: The results showed that platelet lysate had a better and higher performance than other biomaterials in the treatment and healing of leishmanial lesions.